The use of reflection in practice: the experiences of 3rd year Baccalaureus Technologiae (BTech) nursing students at a nursing education institution in the Western Cape Province - Adams, Gayroun (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCur)--Stellenbosch University, 2018.